A novel creep-fatigue stiffness degradation model for composite materials. (1st April 2020) - Samareh-Mousavi, Seyed Sina; Taheri-Behrooz, Fathollah
Abstract: In this paper, a novel creep-fatigue stiffness degradation model for composite materials is introduced. The model proposed a nonlinear stress–strain constitutive equation in the form of a function of time and cycles simultaneously. The presented model consists of a linear elastic component, which is degraded as a function of cycles, and a nonlinear time-dependent component, which combines both time- and cycle-dependent nature of fatigue phenomena in an integrated formulation. The model predictions are validated by the experimental data taken from the literature for short fiber E-glass/polyamide6, 6 and [±45]2s HTA(12 K)/6376 epoxy. It is shown that the model has the capability to predict the stress–strain curve after cycles of loading, taking into account the time-dependent response of composites. It is shown that under high stress levels, the development of fatigue mean strain is dominated by fatigue damages; under lower stress levels, however, the mean strain is mostly controlled by time-dependent viscoelastic strains.